Architectonics of imitation in Spenser, Daniel, and Drayton - Galbraith, David Ian, 1953- (University of Toronto Press, 2000)
Exploring the boundaries between poetry and history on three of England's epic literary works, Galbraith argues that they enter into a dialogue with classical and contemporary predecessors with implications for understanding the English Renaissance.